1989
DOI: 10.1002/hep.1840090210
|View full text |Cite
|
Sign up to set email alerts
|

Anoxic hepatocyte injury: Role of reversible changes in elemental content and distribution†

Abstract: Examination of anoxic isolated hepatocytes by light and electron microscopy indicated that initial morphologic changes were largely localized to the periphery of the cells. This early phase consisted of surface bleb formation but was not accompanied by alterations in parameters of plasma membrane integrity (leakage of cellular enzymes, exclusion of trypan blue). The time course of changes in structure was temporally related to alterations in the elemental distribution and content of various subcellular compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
2
11
0
Order By: Relevance
“…Interestingly, S. flexneri invaded less hepatocytes under hypoxia, in agreement with other studies using different pathogens and cells [29]- [31]. Hypoxia can modify gene expression, intra and extracellular pH as well as membrane receptors [32]- [34]. We can speculate that these factors contributed to the lower entrance of bacteria into hepatocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, S. flexneri invaded less hepatocytes under hypoxia, in agreement with other studies using different pathogens and cells [29]- [31]. Hypoxia can modify gene expression, intra and extracellular pH as well as membrane receptors [32]- [34]. We can speculate that these factors contributed to the lower entrance of bacteria into hepatocytes.…”
Section: Discussionsupporting
confidence: 79%
“…Other studies have also shown that reoxygenation before the rupture of plasma membrane blebs results in the rapid resorption of blebs and in the recovery of hepatocytes, rather than in the accentuation of cellular injury. [34][35][36][37] Conflicting results of the susceptibility of hepatocytes to hypoxia-reoxygenation have been reported by others, 38,39 but these experiments used hepatocyte suspensions which may not be relevant to the physi- cyte cell suspensions, 36,37,39 cells cultured for less than 22 hours, 34,38 or fasted rats as cell donors. 34 All these factors could be the cause of the suboptimal viability of cultured DISCUSSION hepatocytes because of effects on plasma membrane integrity and on antioxidant defences, particularly cellular glutathione In ischemia-reperfusion injury of the liver, the severity of hepatic damage exceeds that produced during a comparable levels.…”
Section: Effect Of Hypoxia-reoxygenation On Secs In Sec/kupffermentioning
confidence: 99%
“…Several findings implicate that the pathogenesis of hypoxic and toxic cell injury to hepatocytes involves intracellular Na C accumulation [1][2][3][4][5]. Total Na C content increases rapidly in all regions of hepatocellular cytoplasm during the first 30 min of anoxia [2].…”
Section: Introductionmentioning
confidence: 99%
“…Total Na C content increases rapidly in all regions of hepatocellular cytoplasm during the first 30 min of anoxia [2]. Moreover, hypoxia, hepatocyte cold storage, respiratory inhibition, uncoupling, the redox cycler menadione all cause an increase of intracellular Na C , which is followed by cell swelling and cell death [3][4][5].…”
Section: Introductionmentioning
confidence: 99%